Design Thinking Sharing as Inspiration for the Hadith of the Prophet SAW - Agung Bayuseto; Agus Suyadi Raharusun (UIN Sunan Gunung Djati Bandung, 2021)
This study aims to discuss the hadith about sharing as a form of concern. This research method uses a qualitative type through literature study and the study of the hadith design thinking approach. The results and discussion of this research include sharing activities (charity), the Prophet Saw. exemplary in sharing, and sharing innovation. This research concludes that the hadith of the Prophet SAW. have inspirational messages in the creative process of sharing that is not limited to anyone